Seed Embryo Development Is Regulated via an AN3-MINI3 Gene Cascade - Meng, Lai-Sheng; Wang, Yi-Bo; Loake, Gary J.; Jiang, Ji-Hong (Frontiers in Plant Science, 2016)
In agriculture, seed mass is one of the most important components related to seed yield. MINISEED3 (MINI3) which encodes the transcriptional activator WRKY10, is thought to be a pivotal regulator of seed mass. In Arabidopsis SHORT HYPOCOTYL UNDER BLUE1 (SHB1) associates with the promoter of MINI3, regulating embryo cell proliferation (both cell division and elongation), which, in turn, modulates seed mass. Furthermore, the recruitment of SHB1 via MINI3 to both its cognate promoter and that of IKU2 implies a two-step amplification for countering the low expression level of IKU2, which is thought to function as a molecular switch for seed cavity enlargement. However, it is largely unknown how embryo cell proliferation, which encompasses both cell division and elongation, is regulated by SHB1 and MINI3 function. Here, we show that a loss of function mutation within the transcriptional coactivator ANGUSTIFOLIA3 (AN3), increases seed mass. Further, AN3 associates with the MINI3 promoter in vivo. Genetic evidence indicates that the absence of MINI3 function suppresses the decrease of cell number observed in an3-4 mutants by regulating cell division and in turn inhibits increased cell size of the an3-4 line by controlling cell elongation. Thus, seed embryo development is modulated via an AN3-MINI3 gene cascade. This regulatory model provides a deeper understanding of seed mass regulation, which may in turn lead to increased crop yields.